EVALUASI PENDIDIKAN ISLAM - Ismail Marzuki; Lukmanul Hakim (Universitas Muhammadiyah Tangerang, 2019)
Education is a conscious effort and responsibility to nurture, guide and direct the growth and development of the lives of students, so that it has the meaning and purpose of an essential life. While the educational process aims to cause desired changes in each student. The desired changes in students include three fields, namely: (1) personal goals and those related to individuals who are learning for the desired changes, both changes in behavior, activities and achievement, and desired growth for participants students; (2) social goals related to people's lives as social beings along with the general dynamics of society; (3) professional goals related to education and teaching as a science, art and profession. The educational process in question is inseparable from several supporting components. One component that is urgent in seeing the success of education is evaluation.